KEDISIPLINAN KERJA PEGAWAI PADA KANTOR SATUAN POLISI PAMONG PRAJA DAN PEMADAM KEBAKARAN KABUPATEN PAMEKASAN - Fitrianti, Rani Nur; Habibi, Nur Syakherul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2022)
Work discipline can be defined as the implementation of management to reinforce organizational guidelines. Good discipline can reflect a person's sense of responsibility for the tasks assigned to him. This will encourage work morale and the realization of good work productivity. This study aims to determine the level of work discipline of employees of the Pamong Praja Police and Firefighters Office of Pamekasan Regency on employee performance, especially employees with State Civil Apparatus (ASN) status. The results showed that from the results of calculations using the t test, it can be concluded that the independent variable of work discipline which consists of preventive discipline and corrective discipline partially has a significant effect on the dependent variable, namely the performance of the Pamong Praja Police Unit and Pamekasan Fire Department employees. And the corrective discipline variable is the variable that has the most dominant influence on the performance of the Pamong Praja Police and Fire Department employees, so that the second hypothesis is also accepted.